WEBVTT
00:00:01.840 --> 00:00:16.600
Add seven 𝑎𝑏 minus two 𝑐 squared 𝑑 squared minus 𝑒 cubed 𝑓 squared to eight 𝑒 cubed 𝑓 squared minus nine 𝑐 squared 𝑑 squared minus five 𝑎𝑏.
00:00:18.270 --> 00:00:23.490
In order to add these two expressions, we need to collect or group the like terms.
00:00:24.660 --> 00:00:29.050
Seven 𝑎𝑏 minus five 𝑎𝑏 is equal to two 𝑎𝑏.
00:00:30.650 --> 00:00:44.460
Negative two 𝑐 squared 𝑑 squared minus nine 𝑐 squared 𝑑 squared is equal to negative 11𝑐 squared 𝑑 squared, as negative two minus nine equals negative 11.
00:00:46.090 --> 00:00:58.790
Negative 𝑒 cubed 𝑓 squared plus eight 𝑒 cubed 𝑓 squared is equal to seven 𝑒 cubed 𝑓 squared, as negative one plus eight is equal to seven.
00:01:00.300 --> 00:01:10.360
This means that our final answer is two 𝑎𝑏 minus 11𝑐 squared 𝑑 squared plus seven 𝑒 cubed 𝑓 squared.
00:01:11.460 --> 00:01:24.600
We could rewrite these three terms in any order as long as the two 𝑎𝑏 is positive, the 11𝑐 squared 𝑑 squared is negative, and the seven 𝑒 cubed 𝑓 squared is positive.
00:01:26.280 --> 00:01:36.520
For example, the answer could also be written seven 𝑒 cubed 𝑓 squared minus 11𝑐 squared 𝑑 squared plus two 𝑎𝑏.